“A New Ruling Class”. The mayors of Buenos Aires Province during the National Reorganization Process in Argentina - Paula Vera Canelo; Juan Pablo Kryskowski (Íconos)
This article describes the recruitment process of Buenos Aires province mayors during the last military dictatorship in Argentina. The profile of the 406 mayors that ruled over 125 towns in the province between March 24 1976 and December 10 1983 is empirically analyzed. This research led to the creation of an original database, which draws from a variety of sources (“Boletin Oficial Provincial”, classified documents, local and national press, interviews). The inquiry led to the following findings: i) this political elite had distinctive features, linked to the wider political and repressive goals of the dictatorship; ii) In a first period a majority of military mayors were appointed in towns considered as a “priority” for repression( densely populated, industrial, seat of important educational institutions or military facilities); iii) the profile of most of these officials was similar to that of other contemporary elites: male, professional, engaged in occupations typical of local public figures and with party affiliations characteristic of “compatible civilian leadership”; iv) the stability of their political careers was favored by traits such as a civilian background, landownership, previous experience in provincial civil service and prior political experience; and v) although the creation of a new ruling class was among the primary goals of the dictatorship, only a few of the Buenos Aires province mayors were able to secure their political survival upon the return of democratic rule.